Study of Molten Salt Corrosion of Superni-75 using Termogravimetric Technique - Sidhu, TS; Prakash, S; Agrawal, RD (Journal of Naval Architecture and Marine Engineering, 2008)
The present study aims to evaluate the hot corrosion behaviour of the Ni-based alloy Superni- 75 in the molten salt environment of Na2SO-60%V2O5 at 900°C under cyclic conditions. The thermogravimetric technique was used to establish the kinetics of corrosion. X-ray diffraction, scanning electron microscopy/energy-dispersive analysis and electron probe microanalysis techniques were used to analyse the corrosion products. Superni-75 has successfully provided the hot corrosion resistance to the given molten salt environment. The hot corrosion resistance of the Superni-75 has been attributed to the formation of uniform, homogeneous and adherent thick layer of the scale consisting mainly of oxides of nickel and chromium, and refractory Ni(VO3)2. These oxides and refractory nickel vanadates have blocked the penetration of oxygen and other corrosive species to the substrate. Keywords: Hot corrosion, nickel-based alloy, superalloy, molten salt environment DOI: 10.3329/jname.v3i2.922 Journal of Naval Architecture and Marine Engineering 3(2006) 77-82